Analysis and Design of LFSR Based Cryptographic Algorithm: Exploring the Potential of Lightweight LFSR-based Cryptographic Algorithms (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Nowadays security has become a great concern in the field of computer science and information technology. In order to protect data from unintended users and to achieve a desirable level of security, several cryptographic algorithms based on various technology have been proposed. Linear Feedback Shift Register (LFSR) may play an important role in the design of such cryptographic algorithms. LFSR based cryptographic algorithms are often lightweight in nature and are more suitable for resource constrain devices. In this paper we present a detailed analysis of LFSR and design of m - sequence LFSR to implement cryptographic algorithms.